Stan finansów publicznych w Polsce i jego wpływ na warunki realizacji stabilnego wzrostu gospodarczego - Baran, Bernadeta (Condition of Public Finance in Poland and it's Influence on Conditions of Realization of Stable Economic Growth, 2006)
The main fiscal policy indicators: fiscal deficit and public debt are at the centre of attention in EU, because the budgetary stabilization affects macroeconomic stability and long run growth. Regulations concerning forming those two indicators subject coordination in EU. Poland, as a member of the Economic Union, was obliged to lower the level of the budgetary deficit. This operation, because of its structural character, will last according to accepted foundation even for year 2007.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 73-82